The History and Prevalence of Cystic Hydatidosis (Hydatid Disease) in Sheep, Goats, Cattle and Camels in Libya: A Review - Mohamed M. Rhagem; Wafa M. Ibrahem; Kawther M. Ibrahem (Research Aspects in Agriculture and Veterinary Science Vol. 3, 2021)
Echinococcus granulosus, a cestode parasite, causes cystic hydatid illness, which is caused by its larval stage. Hydatid cysts are one of the most common parasitic infections in Libya, causing numerous health problems in humans and resulting in financial losses due to the condemnation of infected viscera from slaughtered animals, as well as a reduction in the quality and quantity of other livestock products such as milk, wool, and meat. The adult stage of the parasite is approximately 3-7 mm long with typically three segments as well as other cestodes morphological features and characteristics which help in species diagnosis. Cystic hydatidosis is a disease that affects a wide range of animal species with varying rates of infection, such as sheep (1.6 to 40%), goats (5.6 to 70%), cattle (2.7 to 56%), and camels (2.7 to 48%), according to many abattoir examinations in Libya (2.7 to 48%). Cystic echinococcosis in livestock can be classed as hyper endemic throughout the country based on available abattoir data, as the infection rate in all animal species reached almost 50% or more, meeting WHO standards. It’s difficult to assess the exact economic losses caused by cystic hydatidosis in livestock because all abattoirs lack accurate and up-to-date government records. The diagnosis of the parasite larval stage (hydatid disease) in living intermediate hosts (ante mortem) is primarily based on imaging and serological methods, whereas the examination of hydatid cysts after slaughtering the animals (post mortem) can be based on inspection of several expected infected organs, primarily the liver and lungs, but also the spleen, kidneys, heart, brain, and bones of the animal carcasses. Prevention of cystic hydatid disease focuses mostly on veterinary investigations to reduce the extent and intensity of echinococcosis in definitive host populations, which may indirectly lead to control of hydatid disease prevalence in intermediate host species. Anti-helminthic medications can be used to treat cystic hydatidosis in animals, which is still under investigation. Regular treatment, extreme caution while handling pets or dealing with animal flesh, and vaccination of ruminant intermediate hosts, are all being considered to reduce the level of infection and egg excretion.